Competitiveness and hardiness of weeds: a silver line for crop improvement - Kumar, Bhumesh; Chander, Subhash; Singh, P. K. (Indian Farming, 2018)
Weeds can provide an alternative potential source of important genes for generating abiotic and biotic stress tolerant transgenic crop plants as well as for other aspect of crop improvements. Utilization of weeds as a source of genetic material has certain advantages over the wild species, microorganism or model plant species. Co-existence of weeds and crop plant ensures better chance of success and provides better control over other co-regulated processes. Another benefit of weeds as a source of genetic material can be seen in terms of cost of fitness and yield penalty. As of now, except few successful examples, most of the transgenic hardly showed any success outside greenhouse in actual environment. Reason for such a failure can be ascribed to the dissimilarity of donor and receptor species and the difference in their natural habitats. Relatedness of the weeds and crop plants, and similarity in their habitat further ensures the better chance of survival.